Dentin Matrix Protein 1 Silencing Inhibits Phosphorus Utilization in Primary Cultured Tibial Osteoblasts of Broiler Chicks - Li, Tingting; Geng, Yanqiang; Hu, Yun; Zhang, Liyang; Cui, Xiaoyan; Zhang, Weiyun; Gao, Feiyu; Liu, Zongping; Luo, Xugang (Frontiers in Veterinary Science, 2022)
Three experiments were carried out in the present study to investigate whether dentin matrix protein 1 (DMP1) was involved in regulating phosphorus (P) metabolic utilization in primary cultured tibial osteoblasts of broiler chicks. Experiment 1 was conducted to select the optimal osteogenic inductive culture medium and the optimal induction time in primary cultured tibial osteoblasts of broiler chicks. In experiment 2, the siRNAs against DMP1 were designed, synthesized and transfected into primary cultured tibial osteoblasts of broiler chicks, and then the inhibitory efficiencies of siRNAs against DMP1 were determined, and the most efficacious siRNA was selected to be used for the DMP1-knockdown experiment. In experiment 3, With or without siRNA against DMP1, primary cultured tibial osteoblasts of broiler chicks were treated with the medium supplemented with 0.0, 1.0 or 2.0 mmol/L of P as NaH2PO4 for 12 days. The P metabolic utilization-related parameters were measured. The results showed that the osteogenic induced medium 2 and 12 days of the optimal induction time were selected; Among the designed siRNAs, the si340 was the most effective (P < 0.05) in inhibiting the DMP1 expression; DMP1 silencing decreased (P < 0.05) the expressions of DMP1 mRNA and protein, P retention rate, mineralization formation, alkaline phosphatase activity and bone gla-protein content in tibial osteoblasts at all of added P levels. It is concluded that DMP1 silencing inhibited P utilization and DMP1 was involved in regulating P metabolic utilization in primary cultured tibial osteoblasts of broiler chicks, which provides a novel insight into the regulation of the P utilization in the bone of broilers, and will contribute to develop feasible strategies to improve the bone P utilization efficiency of broilers so as to decrease its excretion.